KONSTRUKSI TASYRI PADA MASA LAHIRNYA MAZHAB FIKIH - Rusdiyah Rusdiyah (Syariah: Jurnal Hukum dan Pemikiran, 2014)
The Islamic law of today has the relationship with the past Islamic law. In the history process, the growth and development of Islamic law show a dynamics of religious though and describe the clash of religious and the development of social and cultural where the law grows. Therefore, is it appropriate if there is a view that Islamic law is something sacred, immutable and rigid. History fact, especially Islamic law in the golden era, will give a reality about tasyri construction or Islamic law legislation and about emergence of mazhab.